2005
DOI: 10.1103/physrevb.72.024414
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of4felectron states in the metal-insulator transition ofPrRu4P12

Abstract: Magnetic excitations of the filled skutterudite PrRu4P12 exhibiting a metal-insulator (M-I) transition at TM−I = 63 K were studied by inelastic neutron scattering experiment. The spectra at temperatures much lower than TM−I are described as well-defined crystal-field excitations. With approaching TM−I, the excitation peaks broaden and shift considerably together with the temperature variation of the carrier number and the atomic displacement in the transition. The 4f-electron state evolve from the well localiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 19 publications
3
72
0
Order By: Relevance
“…6 However, the non-magnetic reference LaRu 4 P 12 did not show a similar transition, although a very similar FS was expected. 4,5 This fact, together with the neutron 7,8 and Raman 9 experiments, strongly suggested the importance of conduction (c)-f electron hybridization in the MI transition. With theoretical considerations, [10][11][12] it is currently believed that a novel charge density wave (CDW) formation is responsible for the MI transition.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…6 However, the non-magnetic reference LaRu 4 P 12 did not show a similar transition, although a very similar FS was expected. 4,5 This fact, together with the neutron 7,8 and Raman 9 experiments, strongly suggested the importance of conduction (c)-f electron hybridization in the MI transition. With theoretical considerations, [10][11][12] it is currently believed that a novel charge density wave (CDW) formation is responsible for the MI transition.…”
mentioning
confidence: 98%
“…Unlike the conventional CDW where the spatial modulation is provided by strong electron-lattice coupling, in the CDW of PrRu 4 P 12 the modulation is provided by the formation of two Pr sublattices, where the crystal field-split 4f level scheme in one sublattice is different from that in the other. [7][8][9] The microscopic nature of the c-f hybridized electronic structure deserves further studies.…”
mentioning
confidence: 99%
“…On the other hand, the spectrum has a shoulder peak in the insulating state, and it becomes broad upon cooling. It is reported that the two Pr sublattices exists in the insulating state in PrRu 4 P 12 [3], thus it might cause the broadening of the spectrum in Pr 0.9 Ce 0.1 Ru 4 P 12 . Furthermore, below 10 K in the low temperature metallic state, the spectrum is drastically changed and the peak maximum in the spectrum splits into two.…”
Section: Methodsmentioning
confidence: 99%
“…Among the filled skutterudites, PrRu 4 P 12 is known to undergo an exotic metal-insulator (M-I) transition due to an unconventional chargedensity-wave formation at 63 K [2], which originates from an interplay between conduction and Pr 4f electrons. The neutron inelastic scattering experiments revealed distinct crystal electric field (CEF) ground states for the two Pr sublattices; one has a singlet and the other has a triplet ground state [3]. In spite of the magnetic ground state for the half of Pr sites, no indication of magnetic ordering has been observed down to 60 mK [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation